Kebocoran Mikro pada Orifis Barier Semen Ionomer Kaca Modifikasi Resin, Semen Ionomer Kaca Modifikasi Resin Nano dan Resin Komposit Core Build Up. - , Tranantika Rakhma; , drg. Wignyo Hadriyanto, MS., SpKG(K), ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to investigate the microleakage in orifice barrier resin modified glass ionomer, resin modified glass ionomer nano and resin composite core build up. This study was used 30 extracted humand mandibullary premolars were divided into 3 groups each consisting of 10 teeth, and 10 teeth for the control group which is divided into 5 teeth for positive control and five teeth for negative control. For the control group did not apply orifice barrier material. All teeth were prepared with the Crown Down technique, and were obturated using Protaper guta perca and resin sealer. After sealer set, about 4mm of gutta percha was removed from root canal orifice and then group I was applied orifice barrier material resin modified glass ionomer, group II was applied resin modifiefd glass ionomer nano and group III was applied resin composite core build up, for positive and negative control groups did not apply orifice barrier materials. All the subject of the research were thermocycled for 500 cycles at temperature 5 Â° and 55 Â° for 30 seconds, then immersed in a methylene blue for 5 days and after that all te subject were sectioned in a mesiodistal direction. Microleakage was measured with microscope stereo with 60x magnification. ANAVA results showed that orifice barier materials resin modified glass ionomer, resin modifiefd glass ionomer nano and resin composite core build up influenced the microleakage of the tooth after root canal treatment. LSD results showed that there were significant differences in microleakage between the orifice barrier resin modified glass ionomer and resin modified glass ionomer nano, and also resin modified glass ionomer nano with resin composite core build up (p <0.05), and there were no difference between the orifice barrier resin modified glass ionomer nano with resin composite core build up (p > 0.05). In this study, it was concluded that aplication of orifice barrier resin modified glass ionomer cement, resin modified glass ionomer cement nano and resin composite core build up influenced the microleakage of the tooth after root canal treatment.